2013
DOI: 10.1007/s00330-012-2612-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial embolisation for the management of obstetric haemorrhage associated with placental abnormality in 40 cases

Abstract: PAE can be performed safely and effectively for patients with PPH and PA and can preserve the uterus in many patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…A recent Finnish retrospective study reported 89% success rate and 9% complication rate (local hematoma and iliac artery rupture) with this procedure [14]. Hwang et al [15] reported on 40 patients with intractable hemorrhage following abnormal placentation and noted a 93% clinical success of arterial embolization to stop bleeding. Only in three patients hysterectomy was required.…”
Section: Arterial Embolizationmentioning
confidence: 97%
“…A recent Finnish retrospective study reported 89% success rate and 9% complication rate (local hematoma and iliac artery rupture) with this procedure [14]. Hwang et al [15] reported on 40 patients with intractable hemorrhage following abnormal placentation and noted a 93% clinical success of arterial embolization to stop bleeding. Only in three patients hysterectomy was required.…”
Section: Arterial Embolizationmentioning
confidence: 97%
“…However, this small study encompassed only patients without antenatal diagnosis of invasive placentation. 61 CONCLUSIONS Placenta accreta is increasing in incidence likely because of the increased rates of cesarean delivery. The antenatal diagnosis of placenta accreta is important to decrease maternal morbidity and mortality.…”
Section: Interventional Radiologymentioning
confidence: 98%
“…Eleven articles reported 177 patients managed with embolisation of the pelvic arteries (Sivan et al 2010;Yu et al 2010;Park et al 2011;Soyer et al 2011;Hwang et al 2013;Meyer et al 2012;Li et al 2012;Bouvier et al 2012;Chung et al 2013;Diop et al 2010;Jung et al 2011): a secondary hysterectomy occurred in 20/177 (11.3%), a subsequent menstruation in 74/85 (87.1%) and a subsequent pregnancy in 3/10 (30%). All patients survived until the end of follow-up.…”
Section: Embolisation Of the Uterine Arteries (Table I)mentioning
confidence: 95%